The use of medications approved for alcohol use disorders in Italy - Fortinguerra, Filomena; Pierantozzi, Andrea; Trotta, Francesco (Frontiers in Public Health, 2023)
Background Italy has the highest per capita alcohol consumption among European countries. Several pharmacological treatments for alcohol use disorders (AUDs) are currently available in Italy, but no consumption data are available. A first analysis of national drug consumption, comprising the whole Italian population over a long-term period covering the COVID-19 pandemic, was performed. Methods To analyze the consumption of medications indicated for therapy of alcohol dependence, different national data sources were used. Consumption was measured as a defined daily dose (DDD) per 1,000,000 inhabitants per day. Results In 2020, the total consumption of medicines used in the treatment of AUDs amounted to 310.3 DDD per 1 million inhabitants per day (0.018% of the overall drug consumption in Italy) with a decreasing gradient from the north (373.9 DDD) to the south (250.7 DDD). 53.2% of the overall doses were dispensed by public healthcare facilities and 23.5% by community pharmacies, while the remaining 23.3% were purchased privately. The temporal trend of consumption seemed to be stable across the last few years, although an impact of the COVID-19 pandemic was observed. Disulfiram was the most consumed medicine over years. Conclusion All Italian regions offer pharmacological treatments to patients with AUDs, but differences in the number of dispensed doses suggest a different local organization of patient care, which can be partly explained by the different severity of the clinical condition of residing patients. Pharmacotherapy of alcoholism should be deeply investigated to describe the clinical characteristics of treated patients (i.e., comorbidities) and evaluate the appropriateness of prescribed medications.